Technology of dialogical learning as a component of future teachers’ professional educatio - Морозов, В. В. (Pedagogy of Higher and Secondary Education, 2012)
Morozov V. V. Technology of dialogical learning as a component of future teachers’ professional education. The article deals with the technology of dialogical training at universities, based on the principle of role prospect.